Classification of settlements on the basis of the ecological situation in the Navoi region and the factors affecting the health of the population - Komilova, Nilufar; Latipov, Normurod (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Formulation of the problem. In today’s age of globalization, the urgent task of socio-economic development is to mobilize the potential of regions to ensure sustainable economic growth within an innovative, socially-oriented development model. Territories are one of the main principles of state development. Decree of the President of the Republic of Uzbekistan No. 60 of January 28, 2022 "On the Development Strategy of the New Uzbekistan for 2022-2026" is particularly important with a focus on optimizing the current environmental situation and public health. Analysis of recent research and publications. In developing countries, the share of industrial production is higher than that of agriculture. Uzbekistan belongs to the classification of developing countries, with a relatively high share of industrial clusters and technology parks in the administrative unit. If we pay attention to the analytical data, the gross domestic product of the Republic in 2017 amounted to 317 476.4 billion soums, in 2019 - 529 391.4 billion soums, and in 2020 - This figure amounted to 605,551.3 billion soums. The share of industry in GDP is 23.5%, 31.4% and 36%, respectively. The aim of the work. Although the Navoi region is considered the smallest administrative unit of our republic, it stands out among the regions in terms of industry and production with huge natural resources. This in itself is the basis for the formation of a negative ecological environment and the emergence of problems related to the health of the population, and from this point of view, the Navoi region and its administrative units were chosen as the object of research. The presence of administrative units with a high share of industry in the country, such as Tashkent, Fergana, Andijan, Samarkand, Navoi, Kashkadarya, has a serious impact not only on the region but also throughout the country. Clearly, local, regional and international cooperation is key to preventing environmental crises, as is the case around the world. If we take the Navoi region alone, it will provide 18% of the republic’s industrial output in 2020 alone, which is the third-largest among the administrative units. But there is another side to the issue, and today the ecological environment in urbanized and highly industrialized cities is deteriorating significantly. As one problem raises another, environmental crisis has a serious impact on the health of the people living in the area, which in turn has an impact on living standards and life expectancy. Research methods. This article uses methods such as comparative analysis and comparison, and direct observation based on the statistical data of the Republic of Uzbekistan. Problems of further research. As a result of the harmonious growth of industry and production, problems related to the environmental condition of cities and the health of the population are becoming widespread. Preventing these problems, and forecasting the future by analyzing the current environmental situation is the main problem. Presentation of the main research material. Studies show that atmospheric air pollution is the most important factor in determining the state of the living environment. The total amount of gases emitted into the atmosphere in the country is 924.4 thousand tons, and the Navoi region accounts for 48.8 thousand tons of these gases or 52.7% of the total. The proximity of large industrial enterprises in the region to residential areas leads to the direct impact of toxic gases on the population, such as external respiration and cardiovascular disorders. The number of patients with respiratory problems in the province increased from 246 in 2019 to 277 in 2021, and the number of patients with the vascular disease increased from 17,400 to 18,300, respectively, indicating a serious concern about atmospheric air problems in the province. Practical value. The practical significance of the work is that it consists of the stabilization of the ecological situation in the region, paying attention to the health of the population and especially children, and presenting proposals and recommendations to the relevant organizations to reduce the number of harmful gases released into the atmosphere. Research results. It should be noted that the development of recommendations to reduce the negative impact of industrial and manufacturing enterprises, transport and other factors on human health and the natural environment is very relevant today.